The mythmakers : the remarkable fellowship of C.S. Lewis & J.R.R. Tolkien - Hendrix, John, 1976- (Abrams Fanfare, 2024)
"The rich worlds of C.S. Lewis's The Chronicles of Narnia and J.R.R. Tolkien's The Hobbit and The Lord of the Rings have enchanted readers both young and old for generations. But before they created these literary landmarks, Lewis and Tolkien were simply two friends who shared a love of stories. The Mythmakers chronicles their lives, from their horrific tour in the trenches of World War I, their first meeting at Oxford in 1929, and the literary discussions of the Inklings, to World War II, the publications of their works, and their legacies. Their personal stories are so intertwined that neither can be easily told without the other....The Mythmakers reveals how these remarkably creative minds influenced each other--their world-building philosophies, their ideas of mythology and faith, and their belief in the truth behind the human imagination. The Mythmakers is a masterful work capturing the extraordinary lives and literary contributions of Liews and Tolkien, two of the most important and influential writers of the 20th century" --Adapted from dust jacket.